Ambulatory surgery - Matteucci, Pablo (Cirugía del Uruguay, 1991)
The authors the main features of an ambulatory surgery programme. By means of this programme patients who are to be operated on under local, regional or general anesthesia, in /ow-complexity operations, are offered the possibility of discharge on the same day of the operation, dealing with post-operative at home. The authors emphasize the fact that this method can be successfully applied in Uruguay, including the Hospital de Clínicas